Influencia del taller “Easy English” en la producción oral del Idioma Ingles de los estudiantes del 1° grado “b” nivel secundario del colegio particular “Simón Bolívar” Tarapoto– 2015 - Garcia Flores, Marie Lisa (2015)
The following study was aimed to determine the influence 'EASY ENGLISH" workshop to improve the oral production of English language. The group was integrated from SIMON BOLIVAR high school students of the first year section “B”. The EASY ENGLISH workshop’s objective is that the student reaches a proper verbal communication. The variable being evaluated during the research was the oral production, which is divided in: fluency, coherence, concordance and grammar as the dependent variable, and the independent variable which is the EASY ENGLISH workshop also divided in: methodology, contents, materials and evaluation. The pretest results have shown that the SIMON BOLIVAR private school students scored low grades before the EASY ENGLISH workshop was applied. Nevertheless, the post test results have shown the students’ grades had a tremendous improvement after the workshop was applied. One of the main causes for the workshop “EASY ENGLISH “significantly influence in the oral production of English is the design of pre-test and post-test and the constructivist theory used for processing, because this considers the use of the communicative approach , using oral activities in situations simulated and contextualized. Consequently, it is shown that EASY ENGLISH workshop had a significant influence during the students schooling